Complementary treatment of headache with ozonized saline solution under micro-bubbling.Presentation of a clinical case (Ozone Therapy Global Journal, 2024)
Headache is one of the most common disorders of the nervous system, yet, despite this, it continues to be underestimated in Europe, sometimes going undiagnosed and consequently untreated. Therapies for headaches include pharmacological treatments, physiotherapy, psychological support therapies, meditation, and other complementary therapies. Among the latter is ozone therapy, in its various forms of systemic administrations (autohemotherapy, infiltrations, rectal insufflations, and ozonized saline solution under microbubbles).This thesis presents a case of a patient suffering from migraines who underwent ozone therapy with ozonated saline solution under microbubbles, evaluating the number of episodes, their intensity, and how the condition has influenced her quality of life. The patient, after fifteen sessions of treatment with ozonated saline solution, has reported significant improvement, with a decrease in the number of headache episodes, pain intensity, and an increase in quality of life.Treatment with ozonated saline solution under microbubbles could be a valid ally for the complementary treatment of headaches, although further studies are needed.